Arsenic removal from alkaline leaching solution using Fe (III) precipitation. Issue 13 (7th June 2019) - Wang, Yongliang; Lv, Cuicui; Xiao, Li; Fu, Guoyan; Liu, Ya; Ye, Shufeng; Chen, Yunfa
ABSTRACT: The alkaline leaching solution from arsenic-containing gold concentrate contains a large amount of arsenate ions, which should be removed because it is harmful to the production process and to the environment. In this study, conventional Fe (III) precipitation was used to remove arsenic from the leaching solution. The precipitation reaction was carried out at the normal temperature, and the effects of pH value and Fe/As ratio on the arsenic removal were investigated. The results show that the removal rate of arsenic is distinctive at different pH values, and the effect is best within the pH range of 5.25–5.96. The removal rate can be further increased by increasing the ratio of Fe/As. When the pH = 5.25–5.96 and Fe/As > 1.8, the arsenic in the solution can be reduced to below 5 mg/L. However, the crystallinity of ferric arsenate is poor, and the particle size is small, most of which is about 1 μm. The leaching toxicity test shows the leaching toxicity of precipitates gradually decreased by the increase of Fe/As. The precipitates can be stored safely as the ratio of Fe/As exceeded 2.5.